Formation Of Harmful Habits in Society and The Effect on The Human Body - Axmedov Qahramon Abdulhamid O’g’li (Zien Journals, 2021)
This article discusses the nature of harmful habits in society and their negative impact on human life, the importance of preventive measures to prevent the younger generation from being exposed to these harmful habits, the formation of a healthy family environment, the negative consequences of harmful habits in educational institutions. The essence of delivery in different forms is highlighted
Keywords: Bad habits; drugs; alcoholism